Immunohistochemical and molecular pathology of ocular uveal melanocytoma: evidence for somatic GNAQ mutations. Issue 7 (17th May 2013) - Mudhar, Hardeep Singh; Doherty, Rachel; Salawu, Abdulazeez; Sisley, Karen; Rennie, Ian G
Abstract : Objective: Intraocular melanocytoma is a rare naevus variant that can be located at the optic disc or within the uvea, and belongs to the group of non-epithelial-associated melanocytic lesions. We wanted to gain an understanding of the role of GNAQ, GNA11 and BRAF V600E in the pathogenesis of uveal melanocytoma and in cases of transformation to uveal melanoma and also to perform a differential immunohistochemical study comparing melanocytoma with uveal melanoma. Methods and results: Two patients were identified with melanocytoma, one of which had transformed to melanoma. In the latter case, the melanocytoma exhibited an immunophenotype that featured nuclear p27 and no HMB45 staining, with very low Cyclin D1 expression compared with the melanoma that featured little nuclear but more cytoplasmic p27 positivity, much higher Cyclin D1 expression and HMB45 positivity. The melanocytomas were negative for CD68 allowing distinction from melanophages. Both melanocytomas and the melanoma harboured mutations in GNAQ, with no mutations of GNA11 or BRAF V600E. Conclusions: GNAQ mutations are present in uveal melanocytomas and in a case of transformation to melanoma, implicating GNAQ-dependent mitogen activation signals, in the pathogenesis of uveal melanocytoma. This assists in explaining why a proportion of uveal melanocytoma can transform to uveal melanoma, known to harbour high-frequency GNAQ mutations at exon 5, codon 209.